Psychological Distress Negatively Affects Self-assessment of Shoulder Function in Patients With Rotator Cuff Tears - Potter, Michael Q. (Clin Orthop Relat Res, 2014)
BACKGROUND: In many areas of orthopaedics, patients with greater levels of psychological distress report inferior self-assessments of pain and function. This effect can lead to lower-than-expected baseline scores on common patient-reported outcome scales, even those not traditionally considered to have a psychological component. QUESTIONS/PURPOSES: This study attempts to answer the following questions: (1) Are higher levels of psychological distress associated with clinically important differences in baseline scores on the VAS for pain, the Simple Shoulder Test, and the American Shoulder and Elbow Surgeons score in patients undergoing arthroscopic rotator cuff repair? (2) Does psychological distress remain a negative predictor of baseline shoulder scores when other clinical variables are controlled? METHODS: Eighty-five patients with full-thickness rotator cuff tears were prospectively enrolled. Psychological distress was quantified using the Distress Risk Assessment Method questionnaire. Patients completed baseline self-assessments including the VAS for pain, the Simple Shoulder Test, and the American Shoulder and Elbow Surgeons score. Age, sex, BMI, smoking status, American Society of Anesthesiologists classification, tear size, and tear retraction were recorded for each patient. Bivariate correlations and multivariate regression models were used to assess the effect of psychological distress on patient self-assessment of shoulder pain and function. RESULTS: Distressed patients reported higher baseline VAS scores (6.7 [95% CI, 4.4–9.0] versus 2.9 [95% CI, 2.3–3.6], p = 0.001) and lower baseline Simple Shoulder Test (3.7 [95% CI, 2.9–4.5] versus 5.7 [95% CI 5.0–6.4], p = 0.001) and American Shoulder and Elbow Surgeons scores (39 [95% CI, 34–45] versus 58 [95% CI, 53–63], p < 0.001). Distress remained associated with higher VAS scores (p = 0.001) and lower Simple Shoulder Test (p < 0.001) and American Shoulder and Elbow Surgeons scores (p < 0.001) when age, sex, BMI, American Society of Anesthesiologists classification, smoking status, tear size, and tear retraction were controlled. CONCLUSIONS: Higher levels of psychological distress are associated with inferior baseline patient self-assessment of shoulder pain and function using the VAS, the Simple Shoulder Test, and the American Shoulder and Elbow Surgeons score. Longitudinal followup is warranted to clarify the relationship between distress and self-perceived disability and the effect of distress on postoperative outcomes after arthroscopic rotator cuff repair. LEVEL OF EVIDENCE: Level I, prognostic study. See the Instructions for Authors for a complete description of levels of evidence.